Sarana dan Prasarana dalam Pelaksanaan Pembelajaran Penjaskes di SMA Se-Kecamatan Pematang Karau Kabupaten Barito Timur - Wisman , Yossita; Maryono (Jurnal Keolahragaan JUARA, 2021)
The purpose of this study was to determine the sports facilities and infrastructure in the implementation of physical education learning in high schools throughout Pematang Karau District, East Barito Regency. This study uses survey methods and interviews with principals and teachers. Research at SMA Negeri 1 and Madrasah Aliyah Pematang Karau, East Barito Regency. The results showed that the facilities and infrastructure in supporting the physical education learning process at SMA Negeri 1 Pematang Karau, East Barito Regency were athletic facilities and infrastructure 10.41%, game facilities and infrastructure 29.06%, gymnastics facilities and infrastructure 33.33%, sports facilities and infrastructure and self-defense infrastructure 13.34%, swimming facilities and infrastructure 0%. The criteria for sports facilities and infrastructure owned by SMA Negeri 1 Pematang Karau, East Barito Regency are in the poor category. The results of research on the potential of sports facilities and infrastructure in supporting the teaching and learning process of physical education in MA Pematang Karau, East Barito Regency are athletic facilities and infrastructure 16.66%, game facilities and infrastructure 22.29%, gymnastics facilities and infrastructure 13.88% , facilities and infrastructure for selfdefense sports 13.34%. Criteria for sports facilities and infrastructure owned by MA Pematang Karau, East Barito Regency is included in the less category. Although the sports facilities and infrastructure in the two schools were categorized as lacking, the teachers made modifications in learning to achieve the learning objectives in the school.